Sertifikat Hak Cipta Atas Film Sebagai Jaminan Fidusia Berkaitan Dengan Benda Bergerak Tidak Berwujud - Krisna, Made Ari Yudia; Dahana, Cokorda Dalem (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022)DO - 10.24843/AC.2022.v07.i03.p14, 2022)
The purpose of this study was to determine and analyze the conditions for applying for bank credit related to copyright on films as collateral objects after the provisions of Article 16 paragraph (3) UUHC and execution of copyright certificates on films as fiduciary guarantees related to default by the debtor. The writing of this journal uses a normative type of research where an assessment of the applicable laws and regulations is carried out and uses secondary data as the main data. Based on the results of the study, it can be concluded as follows: (1) The conditions that are met by the copyright owner are then made a credit agreement followed by a fiduciary guarantee agreement made by a notary and registered at the fiduciary guarantee registration office to obtain a fiduciary guarantee deed; and (2) Execution related to the debtor's default on his film certificate which has been stated in the fiduciary guarantee deed used by public auction or underhand sales in accordance with the agreement of the parties to finance the debt.